Women and Coronary Artery Disease. Part I: Basic Considerations - Abbasi, Seyed-Hesameddin (Tehran University of Medical Sciences, 2011)
Women die of cardiovascular disorders even more than a combination of breast cancer, stroke, chronic obstructive pulmonary disease, and lung cancer. Recent data show that while 1 out of 2.6 women die of coronary artery disease (CAD), only 1 out of 4.6 die from cancer. Whereas some studies show an increase in the age-adjusted mortality of CAD in both women and men, some other studies report an increase in mortality amongst young women. There is a significant decrease in sudden cardiac death in men without significant change in women, and more women die of CAD before their arrival at the emergency room of hospitals than do men. It is, therefore, regrettable that many women and their physicians are not sufficiently aware of the problem and this unawareness is believed to be a major culprit for the existing gender disparities and inaction on the part of women as regards risk modification. What is more, the bulk of our knowledge, preventive measures, diagnostic strategies, and treatment plans are on the basis of studies conducted chiefly in men, when powerful evidence-based gender-specific recommendations call for efforts to enroll more women in order to reach a desirable level of sex representation. Given the significance of CAD assessment in women, it is essential that an acceptable risk score system be devised to estimate the risk of coronary events. The Framingham Risk Score, which has been used for this purpose for a long time, is no longer suitable for women and the Reynolds Risk Score seems to be a more appropriate tool. Finally, from a pathophysiological point of view, endothelial and microvascular dysfunctions are the most salient contributors to the development of CAD in women by comparison with men and they give rise to non-obstructive CAD. Lamentably, most of the relevant studies conducted hitherto have focused predominantly on men; any attempt to redress the balance would be of great value in the endeavors to decrease the risk in women.